PDTM-19. TOCA 511 & TOCA FC: PRE-CLINICAL PROOF OF CONCEPT IN MEDULLOBLASTOMA - Richardson, Angela M (Neuro Oncol, 2017)
Toca 511, a clinical-stage retroviral replicating vector (RRV) encoding an optimized yeast cytosine deaminase (CD) prodrug activator gene, in combination with Toca FC (extended-release 5-fluorocytosine (5-FC)), is designed to produce 5-FU which kills cancer cells and immune-suppressive myeloid cells in the tumor microenvironment, leading to anti-cancer immune activation and long-term survival. This combination treatment is currently under evaluation in an international Phase 2/3 trial in patients with recurrent high-grade glioma. In the present study, we investigated the feasibility of further applying Toca 511 & Toca FC in medulloblastoma, the most common malignant tumor of the pediatric nervous system. Aggressive chemotherapy regimens increase survival in children with this disease; however, systemic toxicity limits efficacy. Here we have initiated the first preclinical studies to evaluate RRV-mediated prodrug activator gene therapy in medulloblastoma. Human medulloblastoma cell lines (HDMB03, DAOY) or patient-derived primary medulloblastoma cells were transduced with RRVs encoding either Emerald green fluorescent reporter (RRV-EMD) or the CD enzyme (RRV-CD). RRV replication in vitro, examined by flow cytometry for EMD fluorescence, showed spread to >90% of cells in culture by day 10 post-inoculation. In contrast to non-transduced or RRV-EMD-transduced controls, RRV-CD-transduced medulloblastoma cells exhibited significant dose-dependent reduction of viability upon exposure to 5-FC, as measured by MTS assay. In vivo, stereotactic intracerebellar implantation of non-transduced HDMB03 cells into nude mice resulted in cell dose-dependent median survival time and eventual 100% lethality at all cell doses tested. In this orthotopic medulloblastoma model, mice with RRV-CD-transduced intracerebellar HDMB03 tumors demonstrated increased survival upon 5-FC treatment, as compared to mice treated with PBS or implanted with non-transduced cells. These results support further investigation of RRV-CD-mediated prodrug activator gene therapy for this pediatric malignancy.